Characteristics of medical costs and resource use in patients with rheumatoid arthritis treated with and without glucocorticoids - Eiichi Tanaka; Eisuke Inoue; Ryoko Sakai; Katsuhiko Iwasaki; Ayako Shoji; Masayoshi Harigai (PLoS ONE, 2025)
Objectives To evaluate medical costs and resource use in patients with rheumatoid arthritis (RA) treated with and without oral or injectable glucocorticoids (GCs) as part of their initial treatment with disease-modifying antirheumatic drugs (DMARDs). Methods Patients included in the Japan Medical Data Center health insurance claims database and diagnosed with RA were considered. The date of the first prescription of a DMARD (index date) after an observable 6-month period (baseline) was used to define follow-up (12 months post-index date) periods. Patients with at least one GC prescription in the follow-up period were included in the GC group, and patients without a GC prescription in the follow-up period were classified as the non-GC group. The primary endpoints were costs for drugs, treatments, and materials per patient in the follow-up period. Drugs were divided into medications for RA or for adverse events (AEs). The secondary endpoints were proportions of patients using the subcategories of each resource. The incidence of hospitalization during the follow-up period was evaluated. Results A total of 1,670 and 1,487 patients with median ages of 51.0 and 50.0 years were evaluated in the GC and non-GC groups, respectively. The costs for drugs, treatments, and materials were significantly higher in the GC group compared with the non-GC group (GC/ non-GC; drug costs for RA and AEs, 2,818 USD/ 1,882 USD; drug costs for RA only, 2,697 USD/ 1,805 USD; treatment costs, 2,365 USD/ 1,860 USD; material costs, 112 USD/ 77 USD; P < 0.05). The resource use in almost all drug and treatment subcategories was higher in the GC group. The incidence of hospitalization was also higher in the GC group. Conclusions Patients with RA treated with GCs in the first year after starting DMARDs tended to use more resources and have higher medical costs than patients not treated with GCs.